Fabrikasi Kawat Baja Pagar Berduri Galvanis Diameter 3 mm Kapasitas 100 m/Jam - Muhammad Rizqi Distiawan; Syamsul Hadi; Satria Dwi Wijaya; Mohammad Arif Dzihni Salim; Immanuel Joseph Isgiarno; Rafi Chozy Asshofi (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
The vulnerability of security in various industrial, agricultural, and infrastructure sectors as well as areas that are not always under supervision is a problem faced. The purpose of fabrication is to obtain galvanized barbed wire fences with a diameter of 3 mm that is rust-resistant. The fabrication method includes: wire drawing through a die (die) from a diameter of 4 mm to 3 mm, passing the wire into molten Zinc at 450oC (hot dip galvanization) for 1 minute, making pieces of wire with sharp barbed ends of 40 mm and 70 mm long, inserting 1 piece of wire barb with a length of 40, and winding 1 piece of wire barb with a length of 70 mm around 3 pieces of wire body at every 15 cm distance of 3.8 turns, passing the barbed wire twist in molten Zinc for 1 minute, rolling the barbed wire, quality and dimension inspection. The fabrication results are in the form of 3 mm diameter galvanized barbed wire fences that are rust-resistant, the total production cost is IDR 11,500/m, and the production process duration is 36 seconds/m which implies that galvanized barbed wire fences can be used for protective fences in various industrial, agricultural, and infrastructure sectors and unsupervised areas.